Examining the use of text and video resources during web-search based learning—a new methodological approach. Issue 1 (3rd April 2022) - Pardi, Georg; Hienert, Daniel; Kammerer, Yvonne
ABSTRACT: The present paper introduces a new methodological approach to capture and analyse the processing and use of text, images, and video content during web-search based learning on the free web. We asked 108 university students to search the web to learn about a natural science topic while recording their eye movements and navigation behaviour. Then, we used the 'reading protocol' software to automatically map participants' fixations to text, images, and video content that they had fixated upon on any information resource retrieved. Moreover, we retraced words from participants' post-search essays to words encountered in fixated text or in transcripts of viewed videos, in order to calculate the degree of overlap. Our results showed that the participants directed their attention significantly longer to text than to video or image resources. Nevertheless, multiple video resources were visited by the great majority of students, underlining the importance of videos in web-search based learning. Regarding the origin of learned concepts, more words included in the post-search essay could be retraced to fixated text than to words contained in transcripts of viewed videos. To conclude, we were able to retrace large parts of students' acquired knowledge to retrieved information resources with our approach.